A toughener material and a method of making the same
Patent Information
- Application Number
- CN202610685994.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-19
- Publication Date
- 2026-08-18
AI Technical Summary
[0004]同时,随着聚丙烯酸酯-碳酸钙增韧剂用量的增加,制得复合材料的缺口冲击强度先呈现提高趋势;但是,当聚丙烯酸酯-碳酸钙增韧剂的用量增加至过大后,制得复合材料的缺口冲击强度又开始出现下降
[0023] This invention, while adding to the existing technology, also introduces aluminum-modified nano-titanium dioxide and maleic anhydride-modified chlorinated polyethylene (MAH-g-CPE). MAH-g-CPE contains polar anhydride groups (MAH), which strongly interact with the Al and Ti active sites on the surface of the aluminum-modified nano-titanium dioxide particles. 3+ It possesses electron-deficient properties, which can form coordination bonds or strong hydrogen bonds with the carbonyl oxygen in maleic anhydride (MAH), significantly enhancing the interfacial bonding between chlorinated polyethylene and aluminum-modified nano-titanium dioxide. The Ti-OH on the surface of nano-titanium dioxide also forms hydrogen bonds or ester interactions with MAH, firmly "anchoring" the elastomer to the particle surface. The polyacrylate-calcium carbonate toughening agent itself is polyacrylate coated with calcium carbonate. MAH can interact with the ester groups of polymethyl polyacrylate and the hydroxyl groups on the surface of calcium carbonate, connecting polyvinyl chloride, polyacrylate-calcium carbonate toughening agent, and aluminum-modified nano-titanium dioxide into a whole interfacial phase, thereby synergistically improving the notched impact performance of the composite material.
Smart Images

Figure CN122587361A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of composite material technology, specifically relating to a toughening agent material and its preparation method. Background Technology
[0002] Polyvinyl chloride (PVC) possesses excellent properties such as flame retardancy, corrosion resistance, insulation, wear resistance, and low cost, making it widely applicable. However, unmodified PVC exhibits poor toughness at room and low temperatures and is notch-sensitive, easily cracking under impact, making it unsuitable for use as building or structural materials. Elastomer toughening modification is commonly employed, which, while significantly improving toughness, sacrifices valuable properties such as rigidity and strength.
[0003] In existing technologies, polyacrylate-calcium carbonate toughening agents are used in rigid polyvinyl chloride (PVC). With increasing amounts of the polyacrylate-calcium carbonate toughening agent, the flexural modulus of the resulting composite material continuously improves. This is because polymethyl polyacrylate (PMPA) has good compatibility with PVC. The surface of nano-calcium carbonate is coated with PMPA, which effectively improves the compatibility between the PVC matrix and nano-calcium carbonate. Furthermore, the PMPA polymer also contains the flexible monomer polybutyl acrylate, which forms a transition layer between the calcium carbonate particles and the matrix, facilitating energy absorption. Since nano-calcium carbonate itself is a rigid particle, its addition improves the rigidity and hardness of the composite material.
[0004] Meanwhile, as the amount of polyacrylate-calcium carbonate toughening agent increases, the notched impact strength of the resulting composite material initially shows an increasing trend; however, when the amount of polyacrylate-calcium carbonate toughening agent increases to an excessive level, the notched impact strength of the resulting composite material begins to decrease again. Summary of the Invention
[0005] To address the problems existing in the background art, the present invention provides a toughening agent material and its preparation method. By increasing the amount of polyacrylate-calcium carbonate toughening agent, the flexural modulus of the obtained composite material is improved, while its notched impact strength is further enhanced.
[0006] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing a toughening agent material, comprising the following steps:
[0007] S1. By weight, add 10.8-11 parts of polyacrylate-calcium carbonate toughening agent, 100 parts of polyvinyl chloride, 3.5-4 parts of stabilizer, 1.3-1.5 parts of aluminum-modified nano titanium dioxide and 2-2.3 parts of maleic anhydride-modified chlorinated polyethylene to a high-speed mixer and stir to mix to obtain a mixed base material.
[0008] S2. The mixed base material obtained in S1 is plasticized and molded by a rubber mixing machine and a flat vulcanizing machine, and then cooled and demolded to obtain the toughening agent material.
[0009] Furthermore, the preparation method of the aluminum-modified nano-titanium dioxide is as follows:
[0010] A1. Pour 10.0 mL of anhydrous ethanol into a beaker, add 6.8 mL of tetrabutyl titanate while stirring, and then stir to mix to obtain the first solution;
[0011] A2. Pour 2.2 mL of acetic acid, 5.2 mL of ethanol, 2.0 mL of 0.1 mol / L aluminum nitrate solution and 1.4 mL of deionized water into a beaker and mix to obtain the second solution;
[0012] A3. Add the first solution obtained in A2 to an acid burette. Under stirring conditions, add the first solution dropwise to the second solution to obtain a mixed solution. After the addition is complete, continue stirring until the mixed solution forms a sol. Let the sol stand for 2-3 days until it forms a gel and then naturally ages until it cracks. Then dry, grind, and calcine to obtain the aluminum-modified nano titanium dioxide.
[0013] Furthermore, in A3, the drying temperature is 80±5℃ and the drying time is 10-15h.
[0014] Furthermore, in A3, the calcination temperature is 500±10℃ and the calcination time is 2-2.5h.
[0015] Furthermore, the preparation method of the maleic anhydride-modified chlorinated polyethylene is as follows:
[0016] B1. By weight, place 100 parts of chlorinated polyethylene (CPE), 4-6 parts of maleic anhydride (MAH), 0.4-0.6 parts of benzoyl peroxide (BPO), 0.3-0.5 parts of caprolactam, and 500-600 parts of toluene in a three-necked flask. Under nitrogen protection, first dissolve the chlorinated polyethylene at room temperature. After the chlorinated polyethylene has completely dissolved, place the three-necked flask in a hot oil bath and stir the reaction at 90-95°C for 2.3-2.6 hours to obtain the product and cool it to room temperature.
[0017] B2. Add the product obtained in B1 to the precipitant acetone, let it stand for 24 hours, discard the solvent, dissolve it in toluene, and then pour it back into acetone to precipitate. Repeat the above operation twice. After the solvent evaporates under an infrared lamp, dry it under vacuum at 50°C to constant weight to obtain the maleic anhydride modified chlorinated polyethylene.
[0018] Further, the preparation method of the polyacrylate-calcium carbonate toughening agent is as follows: Take 400 mL of nano-calcium carbonate slurry with a solid content of 10 wt%, add it to a jacketed reactor, stir, heat to 80°C, and add NaOH solution dropwise until pH=9; weigh 0.4 g of sodium stearate, dissolve it at 80°C, and add it to the reactor to react for 30 min; add polyacrylate emulsion diluent dropwise using a peristaltic pump, controlling the mass ratio of nano-calcium carbonate to polyacrylate to be 10:1. After the dropwise addition is completed, keep the reaction at the temperature for 1 h, and dry to obtain the polyacrylate-calcium carbonate toughening agent.
[0019] Further, the preparation method of the polyacrylate emulsion is as follows: 1.5g of emulsifier (OP-10 and ammonium dodecyl sulfonate in a mass ratio of 2:1), 200mL of deionized water and 10mL of butyl acrylate are added to a 500mL three-necked flask, and pre-emulsified at 75℃ for 30min; 0.1g of ammonium persulfate is added to initiate polymerization until no oily liquid refluxes from the neck of the flask, thus obtaining a butyl acrylate seed emulsion; the temperature is raised to 80℃, 0.05g of ammonium persulfate is added, and 10mL of acrylate and 30mL of methyl methacrylate are added dropwise. The addition is completed in 2h, and 0.05g of ammonium persulfate is added. The temperature is raised to 85℃, and the reaction is continued for 1h. Heating is stopped, and the mixture is cooled to room temperature to obtain the polyacrylate emulsion.
[0020] Furthermore, in S2, the open mill temperature is 165±2℃, and the processing and forming temperature is 185±3℃.
[0021] Secondly, the present invention provides a toughening agent material prepared by the above-described preparation method.
[0022] This application has the following beneficial effects:
[0023] This invention, while adding to the existing technology, also introduces aluminum-modified nano-titanium dioxide and maleic anhydride-modified chlorinated polyethylene (MAH-g-CPE). MAH-g-CPE contains polar anhydride groups (MAH), which strongly interact with the Al and Ti active sites on the surface of the aluminum-modified nano-titanium dioxide particles. 3+ It possesses electron-deficient properties, which can form coordination bonds or strong hydrogen bonds with the carbonyl oxygen in maleic anhydride (MAH), significantly enhancing the interfacial bonding between chlorinated polyethylene and aluminum-modified nano-titanium dioxide. The Ti-OH on the surface of nano-titanium dioxide also forms hydrogen bonds or ester interactions with MAH, firmly "anchoring" the elastomer to the particle surface. The polyacrylate-calcium carbonate toughening agent itself is polyacrylate coated with calcium carbonate. MAH can interact with the ester groups of polymethyl polyacrylate and the hydroxyl groups on the surface of calcium carbonate, connecting polyvinyl chloride, polyacrylate-calcium carbonate toughening agent, and aluminum-modified nano-titanium dioxide into a whole interfacial phase, thereby synergistically improving the notched impact performance of the composite material.
[0024] The Al and Ti sites in aluminum-modified nano-titanium dioxide provide "anchoring points," preventing maleic anhydride-modified chlorinated polyethylene from migrating or detaching. In other words, maleic anhydride-modified chlorinated polyethylene is firmly anchored to the particle surface, forming a stable elastic interface transition layer. The rigid Al and Ti particles bear the load and improve the flexural modulus. The MAH-g-CPE elastomer is responsible for interface buffering, energy dissipation, and inhibiting agglomeration. Thus, the composite material's notched impact performance is synergistically improved. Attached Figure Description
[0025] Figure 1 This is a comparative trend chart of the flexural modulus and notched impact strength test data of toughening agent composite material samples prepared in Examples 1-3 and Comparative Examples 1-4 of the present invention. Detailed Implementation
[0026] The present application will be further described in detail below with reference to the embodiments.
[0027] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application are all commercially available.
[0028] The preparation method of the polyacrylate-calcium carbonate toughening agent involved in the embodiments / comparative examples of the present invention is as follows: 1.5g of emulsifier (OP-10 and ammonium dodecyl sulfonate in a mass ratio of 2:1), 200mL of deionized water and 10mL of butyl acrylate are added to a 500mL three-necked flask, and pre-emulsified at 75℃ for 30min; 0.1g of ammonium persulfate is added to initiate polymerization until no oily liquid refluxes from the neck of the flask, thus obtaining a butyl acrylate seed emulsion; the temperature is raised to 80℃, 0.05g of ammonium persulfate is added, and 10mL of acrylate and 30mL of methyl methacrylate are added dropwise. The addition is completed in 2h, and 0.05g of ammonium persulfate is added. The temperature is raised to 85℃ and the reaction is continued for 1h. Heating is stopped, and the mixture is cooled to room temperature to obtain the polyacrylate emulsion.
[0029] Take 400 mL of nano-calcium carbonate slurry with a solid content of 10 wt%, add it to a jacketed reactor, stir, heat to 80 °C, and add NaOH solution dropwise to adjust the pH to 9; weigh 0.4 g of sodium stearate, dissolve it at 80 °C, and add it to the reactor to react for 30 min; add polyacrylate emulsion diluent dropwise using a peristaltic pump, controlling the mass ratio of nano-calcium carbonate to polyacrylate to be 10:1. After the dropwise addition is complete, keep the reaction at the temperature for 1 h, and dry to obtain polyacrylate-calcium carbonate toughening agent.
[0030] The preparation method of aluminum-modified nano-titanium dioxide involved in the embodiments / comparative examples of this invention is as follows:
[0031] A1. Pour 10.0 mL of anhydrous ethanol into a beaker, add 6.8 mL of tetrabutyl titanate while stirring, and mix to obtain the first solution.
[0032] A2. Pour 2.2 mL of acetic acid, 5.2 mL of ethanol, 2.0 mL of 0.1 mol / L aluminum nitrate solution and 1.4 mL of deionized water into a beaker and mix to obtain the second solution.
[0033] A3. Add the first solution obtained in A2 to an acid burette. Under stirring, add the first solution dropwise to the second solution to obtain a mixed solution. After the addition is complete, continue stirring until the mixed solution forms a sol. Let the sol stand for 2.5 days until it forms a gel and then naturally ages until it cracks. Then dry, grind, and calcine. The drying temperature is 80℃ and the drying time is 13h. The calcination temperature is 500℃ and the calcination time is 2.2h to obtain aluminum-modified nano titanium dioxide.
[0034] The preparation method of maleic anhydride-modified chlorinated polyethylene involved in the embodiments / comparative examples of this invention is as follows:
[0035] B1. By weight, 100 parts of chlorinated polyethylene (Dow CPE 7100), 5 parts of maleic anhydride (MAH), 0.5 parts of benzoyl peroxide (BPO), 0.4 parts of caprolactam, and 550 parts of toluene were placed in a three-necked flask. Under nitrogen protection, the chlorinated polyethylene was first dissolved at room temperature. After the chlorinated polyethylene was completely dissolved, the three-necked flask was placed in a hot oil bath and stirred at 92°C for 2.5 h to obtain the product. The product was then cooled to room temperature.
[0036] B2. Add the product obtained in B1, cooled to room temperature, to the precipitant acetone, let stand for 24 hours, discard the solvent, dissolve in toluene, and then pour into acetone to precipitate. Repeat the above operation twice. After the solvent evaporates under an infrared lamp, dry under vacuum at 50°C to constant weight to obtain maleic anhydride modified chlorinated polyethylene.
[0037] The polyvinyl chloride (Vinnolit S4170AOF from Germany) used in the embodiments / comparative examples of this invention was purchased from Suzhou Zhihuiying New Material Technology Co., Ltd. The lead-barium stabilizer (99% content) was purchased from Handan Fuxing District Aoteng Chemical Trading Co., Ltd.
[0038] Other key aspects of the embodiments / comparative examples of this invention are as follows.
[0039] Example 1: A method for preparing a toughening agent material, comprising the following steps:
[0040] S1. By weight, add 10.9 parts of polyacrylate-calcium carbonate toughening agent, 100 parts of polyvinyl chloride, 3.8 parts of lead-barium stabilizer, 1.4 parts of aluminum-modified nano titanium dioxide and 2.2 parts of maleic anhydride-modified chlorinated polyethylene to a high-speed mixer and stir to mix to obtain a mixed base material.
[0041] S2. The mixed base material obtained in S1 is plasticized and molded using a rubber mixing mill and a flat vulcanizing machine. The initial mixing temperature is 165℃, and the molding temperature is 185℃. After cooling and demolding, the toughening agent material is obtained.
[0042] Example 2: A method for preparing a toughening agent material, comprising the following steps:
[0043] S1. By weight, add 10.8 parts of polyacrylate-calcium carbonate toughening agent, 100 parts of polyvinyl chloride, 3.5 parts of lead-barium stabilizer, 1.3 parts of aluminum-modified nano titanium dioxide, and 2 parts of maleic anhydride-modified chlorinated polyethylene to a high-speed mixer and stir to obtain a mixed base material.
[0044] S2. The mixed base material obtained in S1 is plasticized and molded using a rubber mixing mill and a flat vulcanizing machine. The initial mixing temperature is 165℃, and the molding temperature is 185℃. After cooling and demolding, the toughening agent material is obtained.
[0045] Example 3: A method for preparing a toughening agent material, comprising the following steps:
[0046] S1. By weight, add 11 parts of polyacrylate-calcium carbonate toughening agent, 100 parts of polyvinyl chloride, 4 parts of lead-barium stabilizer, 1.5 parts of aluminum-modified nano titanium dioxide and 2.3 parts of maleic anhydride-modified chlorinated polyethylene to a high-speed mixer and stir to mix to obtain a mixed base material.
[0047] S2. The mixed base material obtained in S1 is plasticized and molded using a rubber mixing mill and a flat vulcanizing machine. The initial mixing temperature is 165℃, and the molding temperature is 185℃. After cooling and demolding, the toughening agent material is obtained.
[0048] Comparative Example 1: The difference between this comparative example and Example 1 is that the amount of polyacrylate-calcium carbonate toughening agent used in the preparation of the toughening agent material is reduced to 10 parts; and aluminum-modified nano-titanium dioxide and maleic anhydride-modified chlorinated polyethylene are not added.
[0049] Specifically, a method for preparing a toughening agent material includes the following steps:
[0050] S1. By weight, add 10 parts of polyacrylate-calcium carbonate toughening agent, 100 parts of polyvinyl chloride and 3.8 parts of lead-barium stabilizer to a high-speed mixer and stir to mix to obtain a mixed base material.
[0051] S2. The mixed base material obtained in S1 is plasticized and molded using a rubber mixing mill and a flat vulcanizing machine. The initial mixing temperature is 165℃, and the molding temperature is 185℃. After cooling and demolding, the toughening agent material is obtained.
[0052] Comparative Example 2: The difference between this comparative example and Example 1 is that aluminum-modified nano-titanium dioxide and maleic anhydride-modified chlorinated polyethylene are not added in the preparation of the toughening agent material.
[0053] Specifically, a method for preparing a toughening agent material includes the following steps:
[0054] S1. By weight, add 10.9 parts of polyacrylate-calcium carbonate toughening agent, 100 parts of polyvinyl chloride and 3.8 parts of lead-barium stabilizer to a high-speed mixer and stir to mix to obtain a mixed base material.
[0055] S2. The mixed base material obtained in S1 is plasticized and molded using a rubber mixing mill and a flat vulcanizing machine. The initial mixing temperature is 165℃, and the molding temperature is 185℃. After cooling and demolding, the toughening agent material is obtained.
[0056] Comparative Example 3: The difference between this comparative example and Example 1 is that maleic anhydride-modified chlorinated polyethylene is not added in the preparation of the toughening agent material.
[0057] Specifically, a method for preparing a toughening agent material includes the following steps:
[0058] S1. By weight, add 10.9 parts of polyacrylate-calcium carbonate toughening agent, 100 parts of polyvinyl chloride, 3.8 parts of lead-barium stabilizer and 1.4 parts of aluminum-modified nano titanium dioxide to a high-speed mixer and stir to mix to obtain a mixed base material.
[0059] S2. The mixed base material obtained in S1 is plasticized and molded using a rubber mixing mill and a flat vulcanizing machine. The initial mixing temperature is 165℃, and the molding temperature is 185℃. After cooling and demolding, the toughening agent material is obtained.
[0060] Comparative Example 4: The difference between this comparative example and Example 1 is that aluminum-modified nano-titanium dioxide is not added in the preparation of the toughening agent material.
[0061] Specifically, a method for preparing a toughening agent material includes the following steps:
[0062] S1. By weight, add 10.9 parts of polyacrylate-calcium carbonate toughening agent, 100 parts of polyvinyl chloride, 3.8 parts of lead-barium stabilizer and 2.2 parts of maleic anhydride modified chlorinated polyethylene to a high-speed mixer and stir to mix to obtain a mixed base material.
[0063] S2. The mixed base material obtained in S1 is plasticized and molded using a rubber mixing mill and a flat vulcanizing machine. The initial mixing temperature is 165℃, and the molding temperature is 185℃. After cooling and demolding, the toughening agent material is obtained.
[0064] Experimental Examples: Toughening agent composite material samples were prepared in Examples 1-3 and Comparative Examples 1-4 of this invention. Test items and standards: ① Impact performance - notched impact strength: tested according to GB / T 1843-2008 "Determination of impact strength of plastic cantilever beams"; ② Flexural performance - flexural modulus: tested according to GB / T 9341-2008 "Determination of flexural properties of plastics". Test results: See Table 1.
[0065] Table 1. Experimental Data
[0066] Example 1 2.37 89.55 Example 2 2.35 89.03 Example 3 2.35 88.95 Comparative Example 1 2.28 88.82 Comparative Example 2 2.33 82.75 Comparative Example 3 2.34 81.16 Comparative Example 4 2.32 86.98
[0067] Results Analysis: Analysis of Examples 1-3, combined with data from Table 1 and... Figure 1 As can be seen, the toughening agent composite material samples prepared by the present invention (Examples 1-3) have a flexural modulus of over 2.35 MPa and a notched impact strength of 88.95 kJ / m. 2 above.
[0068] Combining the data in Table 1 and Figure 1 Analysis of Example 1 and Comparative Examples 1-4:
[0069] Specifically, comparing Comparative Example 1 and Comparative Example 2, it can be seen that compared to Comparative Example 1 using 10 parts of polyacrylate-calcium carbonate toughening agent, Comparative Example 2 increased the amount of polyacrylate-calcium carbonate toughening agent to 10.9 parts. As a result, the flexural modulus of the toughening agent composite sample increased from 2.28 MPa (Comparative Example 1) to 2.33 MPa (Comparative Example 2). However, the notched impact strength decreased from 88.82 kJ / m. 2 (Comparative Example 1) Decreased to 82.75 kJ / m 2 (Comparative Example 2). This shows that increasing the amount of polyacrylate-calcium carbonate toughening agent (10 parts → 10.9 parts) can improve the flexural modulus of the toughening agent composite sample, but it will also lead to a decrease in its notched impact strength.
[0070] Specifically, comparing Comparative Example 2 and Comparative Example 3, it can be seen that, compared to Comparative Example 2, Comparative Example 3, by simply adding aluminum-modified nano-titanium dioxide, did not result in a significant change in the flexural modulus of the toughening agent composite material sample, but the notched impact strength increased from 82.75 kJ / m. 2 (Comparative Example 2) further reduced to 81.16 kJ / m 2 (Comparative Example 3).
[0071] This is mainly because aluminum-modified nano-titanium dioxide is a high-rigidity inorganic particle that forms a dual-rigid particle reinforcement system with nano-calcium carbonate in polyacrylate-calcium carbonate toughening agent. Aluminum-modified nano-titanium dioxide has many surface active sites, which easily form agglomerates with calcium carbonate particles in the polyacrylate-calcium carbonate toughening agent high-filling system, resulting in local stress concentration. The high content of rigid particles increases the brittleness of the system, and cracks can easily propagate rapidly under external force, failing to effectively dissipate energy, leading to a decrease in notched impact strength.
[0072] Specifically, comparing Comparative Example 2 and Comparative Example 4, it can be seen that, compared to Comparative Example 2, Comparative Example 4, by simply introducing maleic anhydride-modified chlorinated polyethylene, did not show a significant change in the flexural modulus of the toughening agent composite sample, but the notched impact strength increased from 82.75 kJ / m. 2 (Comparative Example 2) Increased to 86.98 kJ / m 2 (Comparative Example 4).
[0073] In comparison with Example 1, it can be seen that the simultaneous introduction of aluminum-modified nano-titanium dioxide and maleic anhydride-modified chlorinated polyethylene can produce a synergistic effect, thereby synergistically improving the notched impact strength of the toughening agent composite material sample.
[0074] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.
[0075] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.
Claims
1. A method for preparing a toughening agent material, characterized in that, Includes the following steps: S1. By weight, add 10.8-11 parts of polyacrylate-calcium carbonate toughening agent, 100 parts of polyvinyl chloride, 3.5-4 parts of stabilizer, 1.3-1.5 parts of aluminum-modified nano titanium dioxide and 2-2.3 parts of maleic anhydride-modified chlorinated polyethylene to a high-speed mixer and stir to mix to obtain a mixed base material. S2. The mixed base material obtained in S1 is plasticized and molded by a rubber mixing machine and a flat vulcanizing machine, and then cooled and demolded to obtain the toughening agent material.
2. The method for preparing the toughening agent material according to claim 1, characterized in that, The preparation method of the aluminum-modified nano-titanium dioxide is as follows: A1. Mix 10.0 mL of anhydrous ethanol with 6.8 mL of tetrabutyl titanate to obtain the first solution; A2. Mix 2.2 mL of acetic acid, 5.2 mL of ethanol, 2.0 mL of 0.1 mol / L aluminum nitrate solution and 1.4 mL of deionized water to obtain the second solution; A3. Under stirring conditions, add the first solution dropwise to the second solution and stir until a sol is formed. Let it stand for 2-3 days until the sol forms a gel and then naturally age until it cracks. Then dry, grind, and calcine to obtain the final product.
3. The method for preparing the toughening agent material according to claim 2, characterized in that, In A3, the drying temperature is 80±5℃ and the drying time is 10-15h.
4. The method for preparing the toughening agent material according to claim 2, characterized in that, In A3, the calcination temperature is 500±10℃ and the calcination time is 2-2.5h.
5. The method for preparing the toughening agent material according to claim 1, characterized in that, The preparation method of the maleic anhydride modified chlorinated polyethylene is as follows: B1. By weight, 100 parts of chlorinated polyethylene, 4-6 parts of maleic anhydride, 0.4-0.6 parts of benzoyl peroxide, 0.3-0.5 parts of caprolactam, and 500-600 parts of toluene are placed in a three-necked flask. Under nitrogen protection, the chlorinated polyethylene is first dissolved at room temperature. Then, the three-necked flask is placed in a hot oil bath and stirred at 90-95°C for 2.3-2.6 hours to obtain the product. B2. Add the product obtained in B1 to acetone, let it stand for 24 hours, discard the solvent, dissolve it in toluene and pour it back into acetone. Repeat this process twice, and then dry it to obtain the final product.
6. The method for preparing the toughening agent material according to claim 1, characterized in that, The preparation method of the polyacrylate-calcium carbonate toughening agent is as follows: 400 mL of nano-calcium carbonate slurry containing 10 wt% solids is added to a reaction vessel, stirred, heated to 75-80℃, and the pH is adjusted to 9; 0.4 g of sodium stearate is dissolved at 80℃ and added to the reaction vessel and reacted for 30 min; then, polyacrylate emulsion diluent is added dropwise, controlling the mass ratio of nano-calcium carbonate to polyacrylate to be 10:
1. After the addition is complete, the reaction is kept at the temperature for 1 h, and then dried to obtain the product.
7. The method for preparing the toughening agent material according to claim 6, characterized in that, The preparation method of the polyacrylate emulsion is as follows: 1.5g of emulsifier, 200mL of deionized water and 10mL of butyl acrylate are added to a three-necked flask and pre-emulsified at 75℃ for 30min; 0.1g of ammonium persulfate is added to initiate polymerization until no oily liquid refluxes from the neck of the flask, thus obtaining a butyl acrylate seed emulsion; the temperature is raised to 80℃, 0.05g of ammonium persulfate is added, 10mL of acrylate and 30mL of methyl methacrylate are added dropwise, and another 0.05g of ammonium persulfate is added. The temperature is raised to 85℃ and the reaction is continued for 1h. After cooling to room temperature, the emulsion is obtained.
8. The method for preparing the toughening agent material according to claim 1, characterized in that, In S2, the open mixing temperature is 165±2℃, and the processing and forming temperature is 185±3℃.
9. A toughening agent material, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 8.